Air‐Sea Turbulent Heat Flux Affects Oceanic Lateral Eddy Heat Transport - Weiguang Wu; Amala Mahadevan (Geophysical Research Letters)
Abstract Sea surface temperature anomaly (SSTA) of ocean eddies induces an anomalous air‐sea turbulent heat flux that acts to dampen SSTA. A two‐dimensional SSTA model explores the effect of air‐sea turbulent heat flux, parameterized as SSTA damping, in shaping eddy SSTA patterns. Increased SSTA damping transitions the SSTA pattern from a monopole to dipole, indicating the balance between eddy stirring of the background SST gradient and SSTA damping. The SSTA dipole pattern increases the correlation of eddy velocity and SSTA, but SSTA damping weakens the SSTA, resulting in an optimal damping rate maximizing lateral eddy surface heat transport. Globally, the SSTA damping rate increases toward the equator. In mid‐latitude and high‐latitude regions (e.g., the Kuroshio, the Gulf Stream, and the Southern Ocean), eddy SSTAs are monopoles, while the tropics and subtropics exhibit dipole SSTA patterns due to higher damping rates, facilitating greater lateral eddy heat transport when the SSTA is large.